DETERMINASI TINGKAT KESEHATAN BANK TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Putri, Hestianur; Savitri, Enni; A, Al-Azhar (Universitas Riau, 2021)
This study aims to examine the effect of risk profile on firm value with Good Corporate Governance (GCG) as a moderating variable. The population in this study was banking companies listed on the Indonesia Stock Exchange for the period 2015- 2018. The sampling technique in this study used the purposive sampling technique and obtained a sample of 25 companies. The data analysis method used is multiple linear regression by using SPSS software. The results of this study indicate that the Risk Profile affects firm value, Earnings affect firm value, and Capital affects firm value. Good Corporate Governance (GCG) is able to moderate the influence of risk profile, Earnings, and Capital on firm value.